Out-of-plane anisotropy and low field induced magnetic domain reorientation in Al/Metglas-2605S2/Al trilayer sensors - Passamani, E. C. (2011)
Local magnetism of Al/Metglas-2605S2/Al trilayer-like sensors prepared by dc sputtering has been studied at room temperature by both in-field and zero-field Mo¨ssbauer spectroscopy for amaximum field of 60 mT. Ferromagnetic domain reorientation from out-of-ribbon plane toin-plane, induced by low applied fields, was measured by monitoring the intensities of lines 2 and 5in the Mössbauer sextet spectra obtained for different magnitudes of applied magnetic field.Coating the Metglas-2605S2 with Al layers of 20 lm thickness, a stress-field is induced, allowingto distinguish different in-plane magnetic anisotropy distributions along the ribbon length (4 mT)as well along its width (10 mT). Using a phenomenological model for the magnetization reversal,out-of-plane anisotropies ranging up to 3 kJ/m3 were estimated for the Metglas-2605S2 alloyribbons. This anisotropy range is similar to that observed for the in-plane case previously reported.The methodology applied in this work can be used to determine native out-of-plane anisotropydistributions for different melt-spun ribbons. It also allows understanding magnetization reversalassociated with the ferromagnetic domains reorientation caused either by induced stress or byapplied magnetic field.